1999
DOI: 10.1093/toxsci/51.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a thirteen-week inhalation exposure to ethyl tertiary butyl ether on fischer-344 rats and CD-1 mice

Abstract: The 1990 Clean Air Act Amendments require that oxygenates be added to automotive fuels to reduce emissions of carbon monoxide and hydrocarbons. One potential oxygenate is the aliphatic ether ethyl tertiary butyl ether (ETBE). Our objective was to provide data on the potential toxic effects of ETBE. Male and female Fisher 344 rats and CD-1 mice were exposed to 0 (control), 500, 1750, or 5000 ppm of ETBE for 6 h/day and 5 days/wk over a 13-week period. ETBE exposure had no effect on mortality and body weight wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 24 publications
7
57
1
Order By: Relevance
“…In the 13-week preliminary study preceding the current 2-year study, a significant enhancement of the degree of hyaline droplet accumulation in the renal tubular epithelium was noted in the kidneys of male rats administered 10,000 ppm ETBE in their drinking water. In another study, an increased incidence of α2u-globulin containing protein droplets was reported in male F344 rats exposed to ETBE vapor by inhalation for 13 weeks (Medinsky et al, 1999). These results suggest that the urothelial hyperplasia of the pelvis and the mineral deposition in the renal papilla observed in male rats administered ETBE in the present study resulted from accumulation of α2u-globulin in the renal tubular epithelium.…”
Section: Discussionsupporting
confidence: 74%
“…In the 13-week preliminary study preceding the current 2-year study, a significant enhancement of the degree of hyaline droplet accumulation in the renal tubular epithelium was noted in the kidneys of male rats administered 10,000 ppm ETBE in their drinking water. In another study, an increased incidence of α2u-globulin containing protein droplets was reported in male F344 rats exposed to ETBE vapor by inhalation for 13 weeks (Medinsky et al, 1999). These results suggest that the urothelial hyperplasia of the pelvis and the mineral deposition in the renal papilla observed in male rats administered ETBE in the present study resulted from accumulation of α2u-globulin in the renal tubular epithelium.…”
Section: Discussionsupporting
confidence: 74%
“…Unlike MTBE, there is no direct evidence for ETBE binding to the male‐rat‐specific protein α2u–globulin. However, there is indirect evidence – including evidence that ETBE causes α2u–globulin accumulation in the male rat kidney following inhalation exposure to ETBE (Medinsky et al ., 1999), as well as the reported high male rat kidney/air PC (Kaneko et al ., 2000) – suggesting that, besides solubility in the male rat kidney, there is another process affecting the uptake of ETBE into the tissue. Based on this specific information on MTBE, which is structurally similar to ETBE, along with the fact that other chemicals such as methanol, ethanol, 2‐propanol and 2‐methyl‐2 propanol have similar PCs in the liver and kidney (Meulenberg & Viverberg, 2000), assigning the same value to the kidney/blood PC and the liver/blood PC is warranted.…”
Section: Methodsmentioning
confidence: 85%
“…There is evidence that TBA binds to α2u–globulin (Williams & Borghoff, 2001), but there is no direct evidence that ETBE binds to this protein. However, indirect evidence supports ETBE binding to α2u–globulin, from a study in which ETBE‐exposed male rats developed pathological features associated with α2u–globulin nephropathy (Medinsky et al ., 1999). α2u–Globulin nephropathy is a syndrome associated with chemical binding to α2u–globulin, which results in decreased catabolism of this protein and its accumulation in the kidney in the form of protein droplets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in mice lacking ALDH2 enzyme activity, the DNA damage was detectable even at the lowest dose of ETBE (500 ppm), suggesting that low ALDH2 activity due to genetic polymorphisms may greatly increase the risk of adverse health effects of ETBE. Previous experimental animal studies have shown that substantial damage in liver and kidney is caused by chronic exposure to ETBE at concentrations of 1,750 ppm or higher 10) . However, we suggest that the threshold of toxicity, should be lowered to 500 ppm.…”
mentioning
confidence: 99%